Risk Factors of Postpartum Hemorrhage in Bondowoso District, East Java - Puspitasari, Ratna; Hastuti, Uki Retno Budi; Murti, Bhisma (Journal of Maternal and Child Health, 2017)
Background: Postpartum hemorrhage is the leading cause of the maternal death worldwide. Postpartum hemorrhage accounted 20% of all causes of maternal death in Bondowoso, East Java. This study aimed to examine the risk factors of postpartum hemorrhage.Subjects and Method: This was an analytic observational study using case control design. The study was carried out at 5 community health centers, Bondowoso District, East Java, from March to May 2017. A sample of 120 study subjects were selected for this study by fixed disease sampling, consisting of 40 postpartum women with hemorrhage and 80 postpartum women without hemorrhage. The dependent variable was postpartum hemorrhage. The independent variables were family income, birth space, type of delivery, mothers middle upper arm circumference (MUAC), antenatal visit, and high-risk score card. The data were collected by a set of pre-tested questionnaire. Path analysis was employed for data analysis.Results: Post partum bleeding was directly affected by birth space <2 years or > 10 years (b=3.03; 95% CI = 1.52 to 4.55; p< 0.001), antenatal visit Ã¢â°Â¥ 4 times (b=3.35; 95% CI= 1.82 to 4.87; p< 0.001), High risk score <2 (b=2.18; 95% CI= 0.92 to 3.44; p= 0.001), type of delivery (b=1.63; 95% CI= 0.39 to 2.87; p= 0.010). High-risk score card was affected by birth space <2 years or > 10 years (b=0.80; 95% CI= 0.32 to 1.57; p= 0.041), family income < Rp 1,417,000 (b=0.72; 95% CI= -0.57 to 1.49; p= 0.070), and antenatal visit Ã¢â°Â¥ 4 (b=0.70; 95% CI= -0.07 to 1.48; p= 0.076). MUAC was affected by family income Ã¢â°Â¥ Rp 1,417,000 (b=0.67; 95% CI= -0.08 to 1.44; p= 0.083). Type of delivery (assisted) was affected by high-risk score card <2 (b=1.00; 95% CI = 0.22 to 1.77; p= 0.011) and motherÃ¢â¬â¢s MUAC <23.5 cm (b=1.04; 95% CI= 0.20 to 1.88; p= 0.015).Conclusion: Post partum bleeding was directly affected by birth space, antenatal visit, high risk score, type of delivery. High-risk score card was affected by birth space, family income, and antenatal visit. MUAC was affected by family income. Type of delivery (assisted) was affected by high-risk score cardÃÂ  and motherÃ¢â¬â¢s MUAC.Keywords: postpartum hemorrhage, risk factorCorrespondence:ÃÂ Ratna Puspitasari. Masters Program in Public Helath, Sebelas Maret University, Surakarta. Email: ratnapuspita1987@yahoo.co.id. Mobile: +6285791373311Journal of Maternal and Child Health (2017), 2(2): 177-187https://doi.org/10.26911/thejmch.2017.02.02.08